Review of the genus Ceropria Laporte & Brullé, 1831 (Coleoptera: Tenebrionidae: Diaperinae) from China - Song, Jian; Bai, Xing-Long; Ren, Guo-Dong (Zootaxa, 2024)
The Chinese species of the genus Ceropria Laporte & Brullé, 1831 are reviewed. Twenty-one species are recognized in this study, including two new species: C. cyanecula sp. nov. (Guangxi, Guizhou), and C. viridis sp. nov. (Xizang), and four newly recorded species: C. erythrocnema Laporte & Brullé, 1831 (Yunnan), C. jaegeri Masumoto, 1995 (Xizang, Yunnan), C. merkli Masumoto, 1995 (Yunnan), and C. umbrata (Marseul, 1876) (Shaanxi). Characters of the above mentioned six species are illustrated. All Chinese species of the genus are listed and keyed, and images of the adults are presented.